Office Facilities and Electronic Archives Support (E-Archive) Implications on Quality of Services at The Notary-PPAT Office in Denpasar (Case Study at The Notary-PPAT Office Ni Made Kusuma Dwijayanti, SH., M.Kn) - Ni Nyoman Seri Astini; Kadek Dwi Milleana Dewi; Ida Bagus Gede Udiyana; Ni Ketut Karwini; Ida Bagus Prima Widianta; I Made Kardiana (Universitas Warmadewa, 2022)
The purpose of this study was to determine and analyze the importance of office facilities and Electronic Archives (E-Arsip) on the quality of services at the Notary-PPAT Office of Ni Made Kusuma Dwijayanti, SH., M.Kn. The type of data used in this research is quantitative data with the data source, namely primary data. The collection method is distributing questionnaires to respondents, using classical assumption test analysis techniques, multiple linear regression and hypothesis testing service quality is realized properly if adequate office facilities are used as archive storage places. Using this electronic archive system can save storage space, shorten time. and make it easier to recover archives, and improve archive security, so it doesn't take a long time when the client needs the archived files. The results of the research on office facilities have a positive and significant effect on the quality of services at the Notary Office-PPAT Ni Made Kusuma Dwijayanti, SH., M.Kn., as evidenced by the tcount value of 3.617 and a significant value of 0.001 <0.05. Electronic archives have a positive and significant effect on service quality at the Notary-PPAT Office of Ni Made Kusuma Dwijayanti, SH., M.Kn., as evidenced by the tcount value of 5.790 and a significant value of 0.000 <0.05. Office facilities and electronic archives simultaneously have a significant influence on the quality of services at the Notary-PPAT Office of Ni Made Kusuma Dwijayanti, SH., M.Kn., as evidenced by the F Count value of 94,325 with a significance value of 0.000 < 0.05. From the office facilities variable and the Electronic Archive variable (E-Archive) it can be said that the Electronic Archive variable is more dominant in service quality.